2021
DOI: 10.1111/fog.12555
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal modeling of octopoda paralarvae in the Gulf of Mexico

Abstract: The dynamics and population structure of octopus species in the Gulf of Mexico (GoM) can be studied by analyzing dispersal paralarvae mechanisms. Accordingly, this study focused on understanding octopus paralarval dispersal using numerical modeling. A Lagrangian approach was implemented using the transport model ICHTHYOP and surface currents from a GoM simulation of the HYbrid Coordinate Ocean Model (HYCOM). We modeled the dispersal of four octopus species from the GoM (Octopus “vulgaris”, Octopus insularis, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…During that season, high abundance of, probably, smaller individuals would be also apparent to the north‐west side of the fishing ground. A combination of factors may explain part of these spatial differences including the coupling of the reproductive cycle with the prevailing oceanographic conditions as shown for other merobenthic species (e.g., Otero et al, 2007), reproductive migrations along ontogeny (e.g., Leporati et al, 2015) and, more importantly, the possession of a planktonic paralarvae (Santana‐Cisneros, Rodríguez‐Canul, et al, 2021) that under the influence of westwards transport can settle in distant zones (Santana‐Cisneros, Ardisson, et al, 2021). This leads us to hypothesize that the stock of O. americanus that supports the Yucatan fishery would be probably the result of spawning carried out by populations located in other regions of the Caribbean Sea (e.g., Central America) due to the current transport that affects the region, as it was demonstrated for invasive species in the Gulf of México (Labastida‐Estrada et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…During that season, high abundance of, probably, smaller individuals would be also apparent to the north‐west side of the fishing ground. A combination of factors may explain part of these spatial differences including the coupling of the reproductive cycle with the prevailing oceanographic conditions as shown for other merobenthic species (e.g., Otero et al, 2007), reproductive migrations along ontogeny (e.g., Leporati et al, 2015) and, more importantly, the possession of a planktonic paralarvae (Santana‐Cisneros, Rodríguez‐Canul, et al, 2021) that under the influence of westwards transport can settle in distant zones (Santana‐Cisneros, Ardisson, et al, 2021). This leads us to hypothesize that the stock of O. americanus that supports the Yucatan fishery would be probably the result of spawning carried out by populations located in other regions of the Caribbean Sea (e.g., Central America) due to the current transport that affects the region, as it was demonstrated for invasive species in the Gulf of México (Labastida‐Estrada et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Santana‐Cisneros, Rodríguez‐Canul, et al (2021) showed that O. americanus has a planktonic paralarvae; therefore, it is a merobenthic species as some of its conspecifics (Villanueva & Norman, 2008). Having a planktonic phase would allow this species to undertake vertical migrations and be at the mercy of the currents for later settling in distant areas (Santana‐Cisneros, Ardisson, et al, 2021). This scenario provides arguments to think that individuals of this species could come from the Caribbean Sea and that their recruitment would occur in the eastern part of the Yucatan Shelf as recently hypothesized (Avendaño, Hernández‐Flores, et al, 2020) and in concordance with a hatching period mainly occurring from January to July (Velázquez‐Abunader, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Cresci et al, 2003). Our 2021 awardee, Mariana Santana-Cisneros, modeled the larval dispersal of four species of octopus in the Gulf of Mexico, showing that species-specific fertility, combined with surface temperature and circulation, drove settlement rates and eventual abundances (Santana-Cisneros et al, 2021). We look forward to publishing exciting research by a new, diverse generation of fisheries oceanographers.…”
Section: Virtual Issue Of Most Influential Papersmentioning
confidence: 99%
“…The development of a biological catalogue required the implementation of a wide variety of sampling and analysis techniques. Taxonomic and statistical analysis of samples collected during these oceanographic cruises allowed us to characterize the distribution and abundance patterns of phytoplankton (Linacre et al, 2019;Medina-Goḿez et al, 2019;Medina-Goḿez et al, 2020;Linacre et al, 2021;Ameńdola-Pimenta et al, 2021) fungi (Amend et al, 2019;Vargas-Gastélum et al, 2019), zooplankton (Hereu et al, 2021); ictyoplankton (Daudén-Bengoa et al, 2019;Daudén-Bengoa et al, 2020;Compaire et al, 2021;Santana-Cisneros et al, 2021a;Santana-Cisneros et al, 2021b), demersal fish communities in the water column (Vega Cendejas et al, 2017; Vega-Cendejas and De Santillana, 2019; Aguilar-Medrano and Vega-Cendejas, 2019a; Aguilar-Medrano and Vega-Cendejas, 2019b; Aguilar-Medrano and Vega-Cendejas, 2020b; Aguilar-Medrano and Vega-Cendejas, 2020a), benthic infauna, and invertebrates in the sediments (Hernańdez-Avila et al, 2018;Rubio et al, 2018;Aguilar-Medrano and Vega-Cendejas, 2020b;Torruco et al, 2018;Cisterna-Ceĺiz et al, 2019;Paz-Ríos and Pech, 2019;Hernández-Ávila et al, 2020;Martıńez-Aquino et al, 2020;Paz-Ríos et al, 2020;Soler-Jimenez et al, 2021;Paz-Rıós et al, 2021;Suaŕez-Mozo et al, 2021;Chí-Espínola and Vega-Cendejas, 2022;Quintanar-Retama et al, 2022). Methods for taxonomic identification ranged from the use of morphological techniques to massive sequencing of DNA molecules (metagenomics) and bioinformatic data analysis (Martínez-Aquino et al, 2017;Puch-Hau et al, 2018a;Escobar-Zepeda et al, 2018;Batta-Lona et al, 2019;…”
Section: Baseline Studies and Environmental Variabilitymentioning
confidence: 99%